2021
DOI: 10.1177/0146167220986310
|View full text |Cite
|
Sign up to set email alerts
|

Mind Your Goals, Mind Your Emotions: Mechanisms Explaining the Relation Between Dispositional Mindfulness and Action Crises

Abstract: Action crises describe the intra-psychic conflicts people face when deliberating whether to continue pursuing or to give up a goal for which difficulties keep accumulating. Action crises lead to negative consequences such as elevated distress and depression. Less is known about their predictors. We propose mindfulness as a negative predictor of action crises because mindful people should set more autonomous goals and better regulate their emotions. Three prospective studies examined the relation between mindfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 58 publications
(80 reference statements)
3
12
0
Order By: Relevance
“…It also aligns with previous theoretical propositions and empirical findings by Garland et al (2015Garland et al ( , 2017 that mindfulness meditation increases the use of positive reappraisal coping during stressful events. This finding extends previous research, which had shown that higher dispositional mindfulness helps to prevent action crises (Marion-Jetten et al, 2022), by showing that state mindfulness also helps people regulate their emotions more positively during a visualized action crisis. Our results support further exploration to test the influence of mindfulness on emotion regulation during real, lived, action crises.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…It also aligns with previous theoretical propositions and empirical findings by Garland et al (2015Garland et al ( , 2017 that mindfulness meditation increases the use of positive reappraisal coping during stressful events. This finding extends previous research, which had shown that higher dispositional mindfulness helps to prevent action crises (Marion-Jetten et al, 2022), by showing that state mindfulness also helps people regulate their emotions more positively during a visualized action crisis. Our results support further exploration to test the influence of mindfulness on emotion regulation during real, lived, action crises.…”
Section: Discussionsupporting
confidence: 89%
“…The present study showed that a short mindfulness exercise, in the form of a body scan meditation, enhanced adaptive emotion regulation following the presentation of a personalized action crisis scenario. This finding provides preliminary support for the proposition that mindfulness might also help people cope with action crises as they are happening in the action phase of the Rubicon Model (Marion-Jetten et al, 2022). It also aligns with previous theoretical propositions and empirical findings by Garland et al (2015Garland et al ( , 2017 that mindfulness meditation increases the use of positive reappraisal coping during stressful events.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As previously mentioned, work engagement has three dimensions of vigor, dedication and absorption and it commonly has an inverse relationship with burnout. Many of the work-related health benefits of mindfulness are likely because of its ability to reduce burnout as well as other negative outcomes of demanding or insecure work environments like action crises (Marion-Jetten et al, 2021). This interrelationship between burnout and work engagement is important with one review concluding that burnout is more strongly related to health outcomes, whereas work engagement is more strongly related to motivational outcomes (Bakker et al, 2014).…”
Section: Post-intervention Changes In Mindfulness Stress and Engagementmentioning
confidence: 99%